Low expression of WWC1, a tumor suppressor gene, is associated with aggressive breast cancer and poor survival outcome. Issue 7 (1st June 2019) - Wang, Zhanwei; Katsaros, Dionyssios; Biglia, Nicoletta; Shen, Yi; Fu, Yuanyuan; Tiirikainen, Maarit; Yu, Herbert
Abstract : The WW and C2 domain containing 1 (WWC1) gene encodes a protein named WWC1 (or KIBRA), which is involved in the Hippo signaling pathway. WWC1 is often lost in triple‐negative breast cancer and has been shown to suppress tumor metastasis. In this study, 470 breast cancer patients were recruited and WWC1 expression in the tumor samples was measured with quantitative reverse transcriptase PCR. Associations of WWC1 expression with breast cancer survival were analyzed using the Cox proportional hazards regression model and Kaplan–Meier survival analysis. The relationship between WWC1 expression and methylation was evaluated in a dataset from The Cancer Genome Atlas. Using our microarray data on gene expression and the Ingenuity Pathway Analysis, we predicted the WWC1 ‐associated signaling pathways in breast cancer. Our results showed that low expression of WWC1 was significantly associated with advanced‐stage diseases, high‐grade tumors, and estrogen receptor‐ or progesterone receptor‐negative status. Compared to those with high expression, patients with low WWC1 had higher risk of breast cancer relapse [hazard ratio (HR) = 2.06, 95% confidence interval (CI): 1.26–3.37] and higher risk of death (HR = 2.76, 95% CI: 1.51–5.03). The association with relapse‐free survival remained significant after adjustment for disease stage, tumor grade, and hormone receptor status and was replicated in a public dataset. Analysis of high‐throughput gene expression data indicated that WWC1 was involved in the Hippo signaling pathway. Online data also suggested that DNA methylation was inversely associated with WWC1 expression. The study confirmed that low WWC1 expression was associated with aggressive breast cancer and poor survival outcomes. Abstract : Nearly 70% of triple‐negative breast cancer had a deletion in chromosome 5 (5q11–5q35), which contained WWC1, located in 5q34. WWC1 is known to regulate the Hippo pathway and plays a critical role in suppressing tumorigenesis. We found that low WWC1 expression was associated with poor survival of breast cancer patients, suggesting that WWC1 may be a useful biomarker for breast cancer prognosis.